Effects of preoperative magnesium sulphate on post-cesarean pain, a placebo controlled double blind study. - Seyed Mohamad Mireskandari; Khalil Pestei; Asghar Hajipour; Afshin Jafarzadeh; Shahram Samadi; Omid Nabavian (Tehran University of Medical Sciences, 2015)
To study the role of preoperative intravenous magnesium sulphate in decreasing post-cesarean pain and opioid requirement during first 24hrs.In a double blind randomized clinical trial, prior to induction of general anesthesia, fifty elective cesarean candidates were randomly assigned to one of the two groups of placebo or magnesium sulfate. After surgery visual analogue scale (VAS) and infused morphine by PCA during 24 hrs were recorded. The data were analyzed by mann-Whitney -test, analysis of variance, and student t- test.VAS was significantly lower among patients in the magnesium sulphate group at intervals of 1(st), 6(th) & 12(th) hours after cesarean section (C/S) with the mean scales of (48.9 ± 19.6 VS 74.7 ± 18.4), (42.1 ± 0.9 VS 58.3 ± 16.5) and (25.2 ± 6.1VS 30 ± 8.1) respectively and p-value of < 0.001, 0.002 and 0.05 respectively. However at 24 hrs there was no significant difference in VAS with mean VAS scales of 22.6 ± 4.5 VS 23.6 ± 4.9 and p-value of 0.49. The dose of infused Morphine during 24 hrs was significantly less in the magnesium sulphate group than the placebo group with the means of 4.36 ± 1.4 VS 7.02 ± 1.9 mg respectively (p < 0.001).Administration of bolus 50 mg/kg magnesium sulphate prior to induction of general anesthesia may significantly decreased the morphine requirement during immediate post operative period and can be recommended as one of the modalities of post-operative pain control in the pregnant patients.